Marker assisted pedigree breeding based improvement of the Indian mega variety of rice MTU1010 for resistance against bacterial blight and blast and tolerance to low soil phosphorus. - Laxmi Prasanna B; Dangi K S; Damodar Raju C H; Jagadeeshwar R; Rekha G; Pragya Sinha; Aleena D; Harika G; Mastanbee S K; Swapnil Ravindra K; Kousik M B V N; Mahadeva Swamy H K; et al. (PLoS ONE, 2022)
Rice production is affected by many biotic and abiotic stresses; among them, bacterial blight (BB) and blast diseases and low soil phosphorous stress cause significant yield losses. The present study was carried out with the objective of combining the BB resistance gene, Xa21, the blast resistance gene, Pi54, and the low soil phosphorous tolerance QTL/gene, Pup1, into the genetic background of the Indian mega-rice variety, MTU1010 (Cottondora Sannalu), through marker-assisted pedigree breeding. RP5973-20-9-8-24-12-7 [a near isogenic line (NIL) of MTU1010 possessing Pup1] and RP6132 [a NIL of Akshayadhan possessing Xa21 + Pi54] were crossed and 'true' F1s were identified, using the target gene-specific markers and selfed. F2 plants, which are homozygous for all the three target genes/QTLs, were identified using PCR based markers and were advanced further through the pedigree method of breeding, with selection based on phenotypic traits specific for MTU1010. At the F5 generation, a set of 15 promising triple positive homozygous lines were identified and screened for their resistance against BB and blast diseases and tolerance to low soil P. Among them, two lines (LPK 30-18-16 and LPK 49-15-22) showed higher yields as compared to MTU1010, along with the desirable long slender grain type in both low soil P and normal soil P plots, and also exhibited high levels of resistance against BB and blast diseases, with lesser grain shattering as compared to MTU1010. These lines are being advanced for multi-location trials for validating their performance.